EUROPEAN ORIENTATION OF POLITICAL IDEAS OF METROPOLITAN ILARION: INFLUENCE ON THE STATE FORMATION OF KYIVSKA RUS - Пилипчук, Андрій (SWorldJournal, 2024)
The article explores the political concept of Metropolitan Hilarion, reflecting the socio-political orientations of Kyivska Rus during the reign of Prince Yaroslav the Wise in the 11th century. The appointment of Hilarion as Metropolitan in 1051 and his